Bajki : wybor - La Fontaine, Jean de, 1621-1695.; Kniaznin, Franciszek Dionizy, 1750-1807.; Stepnowski, Adam.; Grandville, J. J., 1803-1847.; La Fontaine, Jean de, 1621-1695. (Warszawa : Panstwowy Instytut Wydawniczy, 1986)
A rhyming selection of La Fontaine's "Fables" in Polish translation from the original French. For children ages 8 to 12.
Translation of: Fables.
Keywords: Fables, French -- Translations into Polish